The Changes of Japanese Attitude toward Law and Legal System: Comparing the Results of the Survey Conducted in 1976, 2005 and 2022 - Kinoshita, Manako (Public Governance, Administration and Finances Law Review, 2023)
This paper compares and analyses the results of a social survey on legal attitudes conducted from January to February 2022 among Japanese citizens (aged 18 or older) nationwide (hereinafter referred to as the 2022 survey) as a follow-up to the 1976 survey and the 2005 survey, which were conducted in previous years. The 2022 survey focused on three lower-level attitudes that constitute legal attitudes: 1. flexibility; 2. naïve moral sentiment (naïve morality); and 3. severe punishment orientation. First, we examined the attitude toward flexibility, especially the legal attitude toward flexibility in contracts. And we found that the majority of respondents in the 2022 survey, regardless of gender or generation, demanded strictness when concluding contracts, but flexibility when executing contracts. This result is almost the same as in the 1976 and 2005 surveys. Regarding the naïve moral sentiment, a change was observed in the 2022 survey, with a decrease among males aged 60 and over and an increase among females in their 20s. The proportion of each pattern accounted for by the combination of flexibility, naïve moral sentiment and severe punishment orientation in the 2022 survey did not differ significantly from the 1976 and 2005 surveys.